Measures for the development and propagation of the Filipino language - Yamio, Teodora Matias 1927- (s.n.], 1959)
This paper presents a study of the measures adopted in the past for the development and propagation of the Filipino Language. A study of these measures may point to a new and better approach to give impetus to the national language project.